(untitled) (Przegląd Religioznawczy – The Religious Studies Review, 2020)
The aim of this article is to present selected phenomena of the exclusive religiosity of Jerzy Hulewicz (1886–1941), that manifested itself through his editorial activity and literature. Publishing (in the years 1917–1922) the first literature magazine in the newly gaining independence Poland he also attempted to show in it not just the purely artistic content, but also neognostic spiritual searches. Hulewicz also developed his religious ideas in the literary works that followed, among which a special attention goes to the drama Kain (1920). In this very work he expressed the idea of a gnostic rebellion most clearly which was one of the constitutive elements of his own religiosity.